2019
DOI: 10.1002/jlb.4vma0318-138r
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors reduce NFAT-dependent expression of antifungal pentraxin-3 by human monocytes

Abstract: Calcineurin (CN) inhibitors are effective clinical immunosuppressants but leave patients vulnerable to potentially fatal fungal infections. This study tested the hypothesis that CN inhibition interferes with antifungal immune defenses mediated by monocytes. We showed that NFAT is expressed by human monocytes, and is activated by exposure to fungal ligands. We confirmed that NFAT translocation potently activated target gene transcription using a human monocytic reporter cell line. Inhibition of CN‐NFAT by cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…These data thus support that Ad-MSCs adopt a PRR-driven response to zymosan that might result in NFAT activation. In fact, we and others have reported that the CN-NFAT pathway is engaged during the PRR-dependent antifungal response ( Bendíčková et al., 2020 ; Goodridge et al., 2007 ) ( Figure 2 F). To verify whether Ad-MSCs engage the CN-NFAT axis in response to zymosan, we again stimulated the cells using the particulate ligand and monitored NFAT subcellular localization by confocal microscopy.…”
Section: Resultsmentioning
confidence: 60%
“…These data thus support that Ad-MSCs adopt a PRR-driven response to zymosan that might result in NFAT activation. In fact, we and others have reported that the CN-NFAT pathway is engaged during the PRR-dependent antifungal response ( Bendíčková et al., 2020 ; Goodridge et al., 2007 ) ( Figure 2 F). To verify whether Ad-MSCs engage the CN-NFAT axis in response to zymosan, we again stimulated the cells using the particulate ligand and monitored NFAT subcellular localization by confocal microscopy.…”
Section: Resultsmentioning
confidence: 60%
“…CN-NFAT activation also occurs in human monocytes exposed to the ligand from Saccharomyces cerevisiae (S. cerevisiae) cell wall - zymosan ( 65 ), and similarly in murine macrophages and DCs after dectin-1 ligation by zymosan or live C. albicans ( 62 ). However, in macrophages exposed to A. fumigatus distinct pathway of TLR9- and phagocytosis-dependent NFAT activation mediated by Bruton’s tyrosine kinase (BTK), but independent on MyD88 has been reported ( 66 ).…”
Section: Nfat Signaling In Myeloid Immune Cells: Is This the Key Pathway Mediating Neutrophil Functions?mentioning
confidence: 99%
“…These clinically successful CNI were also recently repurposed to treat autoimmune disorders [reviewed in ( 59 )] and as cancer chemotherapy considering that several cancer types have constitutively activated and overexpressed NFAT ( 73 , 74 ). However, counterbalancing their potentially beneficial therapeutic role, a growing body of evidence indicates the potential impact of these compounds on myeloid cell function, leading to increased susceptibility to infections ( 59 , 65 , 66 ).…”
Section: Impact Of Immunosuppression On Neutrophil Function and Its Clinical Consequencesmentioning
confidence: 99%
“…Activated CN then dephosphorylates NFAT in the cytoplasm, causing a change in its conformation that exposes a nuclear translocation sequence, leading to initiation of transcription of target genes, including of il2 7,8 . What we now know is that this process does not occur only in T cells, but also in cells of the innate immune system, such as dendritic cells (DC), monocytes and NK cells 9 …”
Section: Introductionmentioning
confidence: 99%